2015
DOI: 10.1093/bja/aev226
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine: review, update, and future considerations of paediatric perioperative and periprocedural applications and limitations

Abstract: Despite lack of paediatric labelling, contributions to the literature on paediatric applications of dexmedetomidine have increased over recent years. Dexmedetomidine possesses many properties that are advantageous for a sedative and anaesthetic; it has been reported to provide sedation that parallels natural sleep, anxiolysis, analgesia, sympatholysis, and an anaesthetic-sparing effect with minimal respiratory depression. In addition, there is increasing evidence supporting its organ-protective effects against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
266
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(281 citation statements)
references
References 126 publications
4
266
1
10
Order By: Relevance
“…Dexmedetomidine is not US FDA labeled for use in patients under 18 years of age; however, it has attained widespread use in pediatric anesthesiology and critical care. It is utilized for postoperative sedation, as a component of total intravenous anesthesia regimens, for opioid-sparing in tonsillectomy, and also for premedication, procedural sedation, prevention of postoperative emergence agitation, and as a component of a balanced general anesthetic technique [33] . Among dexmedetomidine's desirable properties are its ability to maintain normal respiratory patterns, reduce the incidence of postcardiac surgical tachydysrhythmias [34] , and reduce doses of volatile anesthetic agents and opioids when utilized as a component of a balanced anesthetic technique [33] .…”
Section: Dexmedetomidine As a Neuroprotectant In Anesthetic Neurotoximentioning
confidence: 99%
See 1 more Smart Citation
“…Dexmedetomidine is not US FDA labeled for use in patients under 18 years of age; however, it has attained widespread use in pediatric anesthesiology and critical care. It is utilized for postoperative sedation, as a component of total intravenous anesthesia regimens, for opioid-sparing in tonsillectomy, and also for premedication, procedural sedation, prevention of postoperative emergence agitation, and as a component of a balanced general anesthetic technique [33] . Among dexmedetomidine's desirable properties are its ability to maintain normal respiratory patterns, reduce the incidence of postcardiac surgical tachydysrhythmias [34] , and reduce doses of volatile anesthetic agents and opioids when utilized as a component of a balanced anesthetic technique [33] .…”
Section: Dexmedetomidine As a Neuroprotectant In Anesthetic Neurotoximentioning
confidence: 99%
“…It is utilized for postoperative sedation, as a component of total intravenous anesthesia regimens, for opioid-sparing in tonsillectomy, and also for premedication, procedural sedation, prevention of postoperative emergence agitation, and as a component of a balanced general anesthetic technique [33] . Among dexmedetomidine's desirable properties are its ability to maintain normal respiratory patterns, reduce the incidence of postcardiac surgical tachydysrhythmias [34] , and reduce doses of volatile anesthetic agents and opioids when utilized as a component of a balanced anesthetic technique [33] . Dexmedetomidine has a significant body of research and clinical publication in children; a recent PubMed search revealed over 500 publications in children 0-18 years, and 200 in children birth to 2 years of age.…”
Section: Dexmedetomidine As a Neuroprotectant In Anesthetic Neurotoximentioning
confidence: 99%
“…Extreme bradycardia can occur if dexmedetomidine is administered to a patient receiving digoxin, β-adrenergic blockers, calcium channel blockers, and others. Although decreases in HR and a biphasic effect on BP are observed with increasing doses of dexmedetomidine [13].…”
Section: Spots On Prevention Of Emergence Delirium and Agitation In Cmentioning
confidence: 89%
“…9 Sleep architecture during DEX infusion is exclusively non-rapid eye movement (NREM) and is limited to stage 1 and stage 2 sleep. Neither slow wave nor rapid eye movement sleep are observed during DEX infusion.…”
Section: Upper Airway Reflexes Are Preserved During Dexmedetomidine Smentioning
confidence: 99%